Responsiveness to different national interests: voting behaviour on genetically modified organisms in the Council of the European Union - Mühlböck, Monika; Tosun, Jale (Journal of common market studies, 2018)
Does voting behaviour in the Council of Ministers reflect different national interests? In this article, we explore this question by studying requests for authorization of genetically modified organisms (GMOs). The fact that GMOs constitute a highly contentious issue in the European Union enables us to look underneath the ‘culture of consensus’ which usually characterizes voting behaviour in the Council. We argue that the focus on one issue area can help us to discover more specific voting patterns than those that have previously been found in EU legislative studies. Indeed, based on a dataset comprising all authorization requests voted on in the Council between 2004 and 2014, we find that ministers' voting behaviour is significantly influenced by important national factors such as public opinion, party politics, and structural as well as sectoral interests.